PTU-078 Does complex polyps multi-disciplinary team change patients' outcome? district general hospital experience. (June 2019) - Al-Rifaie, Ammar; Bullas, Dominic; Mehmood, Mr RaoKhalid; Smith, Ms Karen; Soliman, Ashraf; Said, Elmuhtady
Abstract : Introduction: The management of advanced non-cancerous GI polyps can be challenging. Data on the impact of complex polyps Multi-disciplinary Team (ComP MDT) is lacking. Our aim is to evaluate the outcomes of ComP MDT in our hospital. Methods: ComP MDT was established in Barnsley Hospital in April 2018 &amp held monthly. Data prospectively collected (Apr2018-Jan2019). ComP MDT team included advanced endoscopists, gastroenterologists and colorectal surgeon. All referrals were received internally with an initial plan. The outcome is approved after discussing each case to reach a consensus. Results: 53 cases discussed in 10 meetings. There were 29 males vs 24 females with a mean age of 68.1 years. 46/53 (87%) were colonic polyps (CP) compared to 7/53 (13%) upper GI polyps (UGIP). The most common indications for referring CP were: multiple polyps ranged from –0 polyps (33%), polyp size ranged 2–0mm (20%), morphology; flat & uncertain pit pattern (20%), difficult colonoscopy; long, loopy & fixed colons (15%) & difficult location (22%). CP were situated mainly in the rectosigmoid 19/46 (41%) vs 17/46 (37%) in the right colon (caecum & ascending colon). ComP MDT agreement with initial endoscopist lesion assessment was observed in 41/53 (78%). However, changes to proposed resection plan were recommended in 21/53 (40%). The range of SMSA score for CP was –4. 26/46 (57%) were level – polyps. Endoscopic mucosal resection (EMR) was approved and achieved in 25/46 (54%). Only one patient had complication with mild postpolypectomy bleeding that was managed conservatively as an inpatient. 6/46 (13%) were referred directly for surgical resection, 3/46 (7%) referred to tertiary centre, 7/46 (15%) were not fit for resection & 5/46 (11%) are awaiting EMR. Recommendations for type of bowel preparation, time dedicated to EMR, type of colonoscope & operating endoscopist were also advised. Out of all CP reviewed at ComP MDT, two found to be cancerous polyps, one successfully removed surgically (confirmed adenocarcinoma) & the other managed conservatively. Polyp type uncertainty was the reason for referring UGIP (5 gastric & 2 duodenal polyps). One gastric polyp resected successfully, three proven hyperplastic histologically & one referred for endoscopic ultrasonography. One duodenal polyp was resected & one directed to cancer pathway. Conclusion: ComP MDT changes the patients' outcome in a significant number of referrals by directing patients to the appropriate intervention. Safe & successful resection of all advanced polyps which deemed resectable on ComP MDT was achieved. ComP MDT was able to pick up some cancerous lesions that were initially misdiagnosed as benign polyps.